Anatomic Variation of Paranasal Sinuses - Simoes, Natália Myrrha; Carneiro, Pollyanna Moura Rodrigues; Silva, Amaro Ilidio Vespasiano; Souza, Paulo Eduardo Alencar de; Manzi, Flávio Ricardo (Journal of Oral Diagnosis, 2017)
Introduction: The sinus are very important on the upper respiratory tract, formed by the ostrich complex (COM) and by the paranasal sinuses. The deep knowledge of the anatomy and variations of the ostium-meatal complex and the paranasal sinuses is a skill expected from the radiologist as well the possible variations with the disease states. Objective: The aim of this study was to evaluate the prevalence of anatomic variations and pathological processes in the paranasal sinuses and the ostiomeatal complex in a population of a large city. Furthermore, association among the presence and localization of anatomic variations and the occurrence of pathological processes was also accessed. Materials and Methods: This study evaluated 1005 CT scans of the sinuses obtained by multislice technique (64 apparatus detectors) with axial and coronal reconstructions, both with 1 and 2 mm thick. Patients of both sexes, aged between 12 and 92 years, who were referred by otolaryngologists were included. Results: Our results showed high prevalence of paranasal sinus CT alterations. The most common were: septal deviation (80.7%), concha bullosa (35.1%), Haller cells (9.6%), and ethmoidal bulla (3.3%). Among the pathological processes, mucoperiosteal thickening associated with acute and chronic inflammation of the sinuses were the most frequent. Ocasionally, it caused obstruction of drainage ostiomeatal complex, in addition to sinusitis (acute and chronic). Odontogenic sinusitis, fungal sinusitis, osteomas, fibrous dysplasia and nasal diseases were also found. There was no association among anatomical variations (changes in the nasal septum, bone spur, concha bullosa, nasal turbinate hypertrophy) and increased chances of obstruction of drainage of frontal, ethmoid and maxillary sinuses. Conclusion: Association between obstruction of the drainage and the occurrence of sinusitis on all paranasal sinuses were also detected. As the population has a high frequency of anatomical variations of the paranasal sinuses, the incorrect interpretation of the images of the sinonasal complex should cause misdiagnosis, compromising patient care. In conclusion, knowledge of the prevalence and characteristics of paranasal sinus CT alterations should be useful for defining specific diagnosis criteria.